Analysis of Risk Management, Visitor Satisfaction, and Destination Accessibility on Tourism Industry Reputation in Bali - I Wayan Adi Pratama; Ni Desak Made Santi Diwyarthi; Bambang Suharto (Westscience Press, 2025)
This study examines the influence of risk management, visitor satisfaction, and destination accessibility on the reputation of Bali’s tourism industry. Utilizing a quantitative approach, data were collected from 140 respondents and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings reveal that visitor satisfaction is the most influential factor, followed by destination accessibility and risk management. Visitor satisfaction significantly enhances the reputation by providing high-quality experiences and fostering positive word-of-mouth. Destination accessibility is vital in ensuring seamless travel and inclusivity, while risk management builds trust through effective safety measures. The study underscores the need for an integrated approach that balances these factors to sustain Bali's position as a leading global tourist destination. Recommendations for policymakers and industry stakeholders are provided to enhance reputation through strategic interventions.